Rapid and sensitive detection of bovine Theileria annulata parasite based on ERA-CRISPR/Cas12a technology - Feng, Xiujuan; Li, Yongchang; Li, Shiyun; zafar, Iqra; Rizk, Mohamed Abdo; Fu, Xianyue; Cui, Zeyun; Zhang, Wei; Zhang, Yang; Hu, Ercha; Guo, Qingyong; Chahan, Bayin (Frontiers in Microbiology, 2025)
Theileria annulata, a globally significant blood parasite in livestock, causes substantial economic losses in resource-limited regions by compromising animal health and hindering the development of the livestock industry. To address this, a rapid, reliable, and sensitive diagnostic assay integrating enzymatic recombinase amplification (ERA) with CRISPR/Cas12a technology was developed. This assay enables visual interpretation through multiple detection modalities, including UV and blue light illumination. Among three primer pairs and two CRISPR RNA (crRNA) candidates screened, the F3/R3 primer set combined with crRNA1 demonstrated the best performance. The optimized ERA protocol achieved complete amplification within 20 min at 37°C. This assay exhibited high specificity for T. annulata detection, with a sensitivity limit of 10 copies/μL, a 100-fold greater sensitivity than conventional PCR, while completing detection within 40 min. Validation of 51 bovine blood samples from a farm in Turpan, Xinjiang, revealed that PCR detected 12 positive cases (23.5% prevalence), whereas the ERA-CRISPR/Cas12a system identified 15 positive cases (29.4% prevalence). The enhanced detection capability of this integrated method provides crucial technical support for field applications in resource-limited settings, effectively addressing the urgent need for rapid and accurate diagnosis of bovine theileriosis.